2010
DOI: 10.1016/j.ajo.2009.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Ocular Manifestations, and Survival in Children with Neuroblastoma: A Population-Based Study

Abstract: Purpose To determine the incidence, ophthalmic manifestations, and survival among children with neuroblastoma in a defined population. Design Population-based retrospective cohort. Methods The medical records of all pediatric (< 19 years) residents of Olmsted County, Minnesota diagnosed with neuroblastoma from January 1, 1969, through December 31, 2008, were retrospectively reviewed. Results Fourteen children were diagnosed with neuroblastoma as residents of Olmstead County, Minnesota, during the 40-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
1
34
0
2
Order By: Relevance
“…Interestingly, each of these three fish harbored metastases in the orbit (Figures 3A, 3D, 3J, 3P and S4B), a metastatic site in children with neuroblastoma that is associated with a poor prognosis (Ahmed et al, 2006; Maris et al, 2007; Smith et al, 2010). We also identified metastases in the gill [functions in oxygen exchange, analogous to the mammalian lung (Menke et al, 2011)] (Figures 3A, 3E, 3K, 3Q and S4C) and spleen [analogous to the mammalian lymph node (Renshaw and Trede, 2012)] of transgenic fish expressing both MYCN and LMO1 (Figure 3A, 3F, 3L and 3R).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, each of these three fish harbored metastases in the orbit (Figures 3A, 3D, 3J, 3P and S4B), a metastatic site in children with neuroblastoma that is associated with a poor prognosis (Ahmed et al, 2006; Maris et al, 2007; Smith et al, 2010). We also identified metastases in the gill [functions in oxygen exchange, analogous to the mammalian lung (Menke et al, 2011)] (Figures 3A, 3E, 3K, 3Q and S4C) and spleen [analogous to the mammalian lymph node (Renshaw and Trede, 2012)] of transgenic fish expressing both MYCN and LMO1 (Figure 3A, 3F, 3L and 3R).…”
Section: Resultsmentioning
confidence: 99%
“…1 Neuroblastic tumors, derived from primordial neural crest cells, are characterized by defective catecholamine synthesis, frequently resulting in the accumulation and excretion of the catecholamine metabolites homovanillic acid (HVA) and vanillylmandelic acid (VMA). 2,3 Landmark papers concerning the use of urine catecholamine samples to detect neuroblastoma and related neural crest tumors have estimated that urinary levels of HVA and VMA were elevated in approximately 90–95% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The important role ophthalmologists have in the detection and management of neuroblastoma is underscored by the numerous ocular manifestations of this disease, including proptosis, 1,79 periorbital ecchymosis, 1,79 Horner syndrome, 5,6,1014 opsoclonus/myoclonus, 15 ocular motility defects, 7,16 ptosis, 16 and blindness8, 17 Of special ophthalmic interest has been the detection of underlying neuroblastoma in cases of pediatric Horner syndrome, including the role urine catecholamine levels have in the recommended ophthalmic work-up. 1,5,6,1012,14,18,19 The purpose of this paper is to report the percentage of neuroblastoma cases presenting with elevated catecholamine levels among a cohort of patients < 19 years diagnosed as residents of Olmsted County, Minnesota, over a defined 40-year period, and to suggest an ophthalmic work-up in cases of idiopathic pediatric Horner syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of 56 children presenting with Horner syndrome, none of the 4 cases of neuroblastoma had elevated urinary catecholamines [15]. Another review found 10 of 14 patients with mean age of 22 months to have elevated VMA and homovanillic acid (HVA), but 3 of the 4 cases without elevated catecholamines were diagnosed with stage IV neuroblastoma [16]. Although this patient had slightly elevated catecholamines, these studies highlight the importance of thorough physical exam and imaging.…”
Section: Discussionmentioning
confidence: 95%